Chinese consumer attitude and purchase intent towards green products. Issue 2 (27th May 2014) - Tang, Yiming; Wang, Xiucun; Lu, Pingping
Abstract : Purpose: – The purpose of this paper is to examine how Chinese consumer attitude mediates factors that influence their purchase intention toward low-displacement vehicles. Design/methodology/approach: – This study utilizes online survey data in China, multiple regression and recursive regression models. Findings: – Consumers' environmental concern, perceived effectiveness belief and functional value positively affect their attitude toward such products. Consumer attitude positively affects purchase intention. Consumer attitude fully mediates the influence of environmental concern, and partly mediates the effect of perceived effectiveness belief, and functional value on purchase intention. Consumers' awareness of government policy is not associated with attitude or purchase intention. Originality/value: – This is a first empirical study to systematically examine Chinese consumer attitude's mediation effect on factors influencing their purchase intent toward low-displacement vehicles in China.